190k views
4 votes
Step 1 ⇒ x - 3 = 3(x + 3)

Step 2 ⇒ x - 3 = 3x + 9
Step 3 ⇒ x = 3x + 12
Step 4 ⇒ -2x = 12
Step 5 ⇒ x = -6

Identify the property of equality which yields Step 5.

2 Answers

5 votes

Answer:

the answer is property of division

Explanation:

look at step 4 then compare it to step 5 how 12 got divided by

User Evan Anderson
by
5.1k points
5 votes

In step four, you'd divide each side by -2 to isolate x

By dividing both sides by -2, you are using the property of equality and it gets you to the answer in Step 5.

User Enjoli
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.